Agricultural exploitation impact on the quality of natural waters in the trout-breeding region of the Mantiqueira ecological corridor (Acta Scientiarum. Biological Sciences, 2014)
Seasonal assessment of water quality was undertaken in an agricultural cattle-raising and trout-breeding region. Seventeen sites were sampled in ten municipalities close to the Papagaio and Ibitipoca State Parks in Minas Gerais, Brazil. Landsat 5 satellite images and Spotmap mosaic images with resolution of 2.5 m were employed to correlate classes of land use and topographic characteristics with the environmental contamination index of the water bodies at these sites. Results show a change in hydric classification of three sites evaluated. During the rainy season, sites 3, 7 and 17 were classified as class 3 according to CONAMA regulations, whereas the other sites were classified as class 2. During the dry season, sites 10 and 11 belonged to class 3 and the others to class 2. Literature and analysis of images and visits on the area showed that the principles of sustainable farming were not being followed in the region. Current research may be a tool for planning the preservation of natural resources. Results indicate there is a need for specific planning for fish farming and agriculture in the region for its sustainable economic exploitation.